The Type of Forage Substrate Preparation Included as Substrate in a RUSITEC System Affects the Ruminal Microbiota and Fermentation Characteristics - Duarte, Andrea C.; Holman, Devin B.; Alexander, Trevor W.; Durmic, Zoey; Vercoe, Philip E.; Chaves, Alexandre V. (Frontiers in Microbiology, 2017)
In vitro fermentation systems such as the RUSITEC are frequently used to assess dietary manipulations in livestock, thereby limiting the use of live animals. Despite being in use for nearly 40 years, improvements are continually sought in these systems to better reflect and mimic natural processes in ruminants. The aim of this study was to evaluate the effect of forage preparation, i.e. frozen minced (FM) and freeze-dried and ground (FDG), on the ruminal microbiota and on fermentation characteristics when included as a substrate in a RUSITEC system. A completely randomised design experiment was performed over a 15-d period, with 7 d of adaptation and an 8-d experimental period. Fermentation parameters (total gas, CH4 and volatile fatty acid production) were analysed on a daily basis over the experimental period and the archaeal and bacterial microbiota (liquid-associated microbes [LAM] and solid-associated microbes [SAM] was assessed at 0, 5, 10, and 15 d using high-throughput sequencing of the 16S rRNA gene. Results from this study suggested a tendency (P = 0.09) of FM treatment to increase daily CH4 (mg/d) production by 16.7% when compared with FDG treatment. Of the major volatile fatty acids (acetate, propionate and butyrate), only butyrate production was greater (P = 0.01) with FM treatment compared with FDG substrate. The archaeal and bacterial diversity and richness did not differ between the forage preparations, although feed particle size of the forage had a significant effect on microbial community structure in the SAM and LAM samples. The Bacteroidetes phylum was more relatively abundant in the FM substrate treatment, while Proteobacteria was enriched in the FDG treatment. At the genus-level, Butyrivibrio, Prevotella, and Roseburia were enriched in the FM substrate treatment and Campylobacter and Lactobacillus in the FDG substrate treatment. Evidence from this study suggests that forage preparation affects CH4 production, butyrate production, and the structure of the rumen microbiota during in vitro fermentation.